HLA antigen, allele and haplotype frequencies and their use in virtual panel reactive antigen calculations in the Finnish population. Issue 1 (6th December 2012) - Haimila, K.; Peräsaari, J.; Linjama, T.; Koskela, S.; Saarinenl, T.; Lauronen, J.; Auvinen, M.‐K.; Jaatinen, T.
Abstract The human leukocyte antigen (HLA) antigen, allele and haplotype frequencies of the Finnish population are quite unique because of a rather restricted and homogeneous gene pool. This has a strong influence on finding suitable donors for transplant patients; hence knowledge about the HLA frequencies of the patient population is essential. Here we report the HLA antigen frequencies for a large population sample and show high resolution HLA allele frequencies for 11 loci, including the rarely typed DPA1 and DQA1 loci. Furthermore, the most common Finnish high resolution haplotypes are presented for five HLA loci. The study shows that there are fewer HLA haplotypes in the Finnish population compared with mixed populations, and the common Finnish HLA haplotypes are more frequent. Using HLA antibody identification and panel reactive antibody calculations we show that a virtual population‐specific panel, combined with single antigen testing, gives a more accurate and reliable estimate of the reactivity of the recipient serum against potential solid organ donors within the Finnish population. The results can be directly used to improve donor search for patients waiting for stem cell transplantation and to allocate highly immunised patients accurately to acceptable mismatch programs.